Transnational Contexts of Development History, Sociality, and Society of Play
XV, 243 p. 32 illus. in color.
Keywords: This book examines the development and prominence of video games within historical, industrial, and social contexts of East Asia, the largest global market for the video game industry. The book overviews the history of video game technology and industry, examines recent trends in mobile social games, and discusses social impacts of video games in East Asian contexts. The first part overviews the history of video game industry and the technological landscape of video games. The second part examines the recent trend in social mobile games and how developers and players interact in this new gaming sphere. The last part of the book discusses the social impacts of video games in East Asian context through both quantitative and qualitative lenses.